Comparing neoadjuvant chemotherapy with or without radiation therapy for pancreatic ductal adenocarcinoma: National Cancer Database cohort analysis. Issue 5 (8th February 2022) - Oba, Atsushi; Wu, Y H Andrew; Colborn, Kathryn L; Karam, Sana D; Meguid, Cheryl; Al-Musawi, Mohammed H; Bao, Quoc R; Gleisner, Ana L; Ahrendt, Steven; Schulick, Richard D; Del Chiaro, Marco
Abstract: Background: Neoadjuvant treatment is important for improving the rate of R0 surgical resection and overall survival outcome in treating patients with pancreatic ductal adenocarcinoma (PDAC). However, the true efficacy of radiotherapy (RT) for neoadjuvant treatment of PDAC is uncertain. This retrospective study evaluated the treatment outcome of neoadjuvant RT in the treatment of PDAC. Methods: Collected from the National Cancer Database, information on patients with PDAC who underwent neoadjuvant chemotherapy (NAC) and pancreatectomy between 2010 to 2016 was used in this study. Short- and long-term outcomes were compared between patients who received neoadjuvant chemoradiotherapy (NACRT) and NAC. Results: The study included 6936 patients, of whom 3185 received NACRT and 3751 NAC. The groups showed no difference in overall survival (NACRT 16.1 months versus NAC 17.4 months; P = 0.054). NACRT is associated with more frequent margin negative resection (86.1 versus 80.0 per cent; P < 0.001) but a more unfavourable 90-day mortality than NAC (6.4 versus 3.6 per cent; P < 0.001). The odds of 90-day mortality were higher in the radiotherapy group (odds ratio 1.81; P < 0.001), even after adjusting for significant covariates. Patients who received NACRT received single-agent chemotherapy more often than those who received NAC (31.5 versus 10.7 per cent; P < 0.001). Conclusion: This study failed to show a survival benefit for NACRT over NAC alone, despite its association with negative margin resection. The significantly higher mortality in NACRT warrants further investigation into its efficacy in the treatment of pancreatic cancer. Abstract : This study of pancreatic cancer using National Cancer Database data demonstrates that neoadjuvant chemoradiotherapy is associated with a higher 90-day mortality rate than, and fails to show survival benefit over, neoadjuvant chemotherapy, despite its association with a higher rate of margin-negative resection. This implies that radiotherapy should not be considered as a standard neoadjuvant treatment at this time.